2022
DOI: 10.1177/13623613211062952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on sleep, melatonin level, and behavioral functioning in children with autism

Abstract: Poor sleep quality and low behavioral functioning are commonly reported in children with autism spectrum disorder. This study examined the impact of exercise on sleep on melatonin level and behavioral functioning in the population. Children with autism spectrum disorder( n = 55; age = 10.97 ± 1.90) were randomly allocated to a morning jogging intervention group or a control group. Participants’ sleep was measured using actigraphy and sleep log assessments. Twenty-four-hour and first morning urinary 6-sulfatoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Research revealed a significant improvement in sleep efficiency and reduction in wake after sleep onset time in the intervention group but not in the control group [ 13 ]. Similar sleep benefits following physical exercise were also evident in a more recent study [ 14 ], where we showed that jogging intervention had significantly improved sleep efficiency and sleep duration in children with ASD. More remarkably, we also observed that the endogenous melatonin level, as reflected by the 6-sulfatoxymelatonin (aMT6s), was significantly increased within the jogging intervention group, while no change was found in the control group.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Research revealed a significant improvement in sleep efficiency and reduction in wake after sleep onset time in the intervention group but not in the control group [ 13 ]. Similar sleep benefits following physical exercise were also evident in a more recent study [ 14 ], where we showed that jogging intervention had significantly improved sleep efficiency and sleep duration in children with ASD. More remarkably, we also observed that the endogenous melatonin level, as reflected by the 6-sulfatoxymelatonin (aMT6s), was significantly increased within the jogging intervention group, while no change was found in the control group.…”
Section: Introductionsupporting
confidence: 87%
“…Endogenous melatonin level . The endogenous melatonin level of the participants, reflected by the 6-sulfatoxymelatonin (aMT6s, creatinine-adjusted morning urinary melatonin representative), will be measured from their 24-h and first morning urinary samples during weekend and Monday respectively [ 14 ], and the participants will be required to stay at home for sample collection. All urine samples will be collected using 24-h and first morning void urine bottles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous knowledge on the effect of physical exercise on endogenous melatonin production is controversial as it has been shown that melatonin levels can increase, decrease, or remain unaffected by exercise ( 55 , 56 ). On the other hand, physical exercise has been suggested as a synchronizer of the circadian system, making it a potential treatment for circadian rhythm misalignment ( 55 , 57 , 58 ). As a result, exercise may be an accessible non-pharmacological intervention of special interest when treating ASD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity implies multiple benefits, such as the prevention of cardiovascular diseases [ 12 ], better control of body weight [ 10 , 13 ], less presence of chronic pain [ 14 ], better bone density and better physical fitness [ 15 , 16 ], greater muscle strength, and lower risk of mortality [ 13 , 17 , 18 ]. In addition, at a psychological level, physical activity improves mental health and quality of life [ 8 , 19 ], reduces stress and anxiety [ 8 , 20 , 21 ], lowers the risk of depression [ 22 ], and improves the quality of sleep [ 23 ]. Likewise, physical activity is positively related to better academic performance among university students [ 24 ].…”
Section: Introductionmentioning
confidence: 99%